Gerenciamento de resultados em processos de fechamento do capital em empresas brasileiras - Cecilia Ferreira Chaves (2021)
The research analyzed earnings management practice prior to delisting in Brazilian nonfinancial companies between 2002 and 2020. It used unconsolidated financial statements corrected by inflation in the years ended immediately before the date of the cancellation announcement, and from the second previous year. Data were used in cross-section and earnings management was measured from the perspective of discretionary accruals, estimated by adaptations of the Modified Jones Model, proposed by Dechow, Sloan, and Sweeney (1995) - and of the Collins, Pungaliya, and Vijh Model (2017). Earnings Management was also analyzed from the real activity manipulation perspective, according to Roychowdhury's (2006) model. Companies were classified according to the reason for closing: OPA made by the controlling shareholder or by the company itself; takeover bid for the sale of control; OPA waiver; Acquisitions; Bankruptcy and Cancellation by non-compliance with the regulations. As evidence, Brazilian companies manipulate their accounting information through discretionary accruals and/or actual activities in at least one of the two years before the delisting announcement. In addition, the type of delisting has a statistically significant relationship with the practice of earnings management. Concerning the control variables used, it was possible to verify in all estimates a negative relationship between IFRS adoption and management by production level and company size and management through discretionary spending decisions Finally, earnings management levels were compared between companies that went private and companies that remained publicly traded, and as a result, no evidence was obtained that companies from the prior group manipulate their earnings more than companies in the latter. As relevant contributions to the research of the area, this work analyzed earnings management from the perspective of accruals and real decisions and associated them with the types of closure allowed in Brazilian standards.